2021
DOI: 10.1111/dom.14451
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of glucose‐lowering medications on body weight and blood pressure in patients with type 2 diabetes: A systematic review and network meta‐analysis

Abstract: Aim To compare the effects of glucose‐lowering drugs on body weight and blood pressure in adults with type 2 diabetes. Methods We searched Medline, Embase, the Cochrane Library, and grey literature sources until 29 September 2020 for randomized controlled trials of at least 24 weeks' duration assessing the effects of glucose‐lowering drugs on body weight and blood pressure in adults with type 2 diabetes. We performed frequentist network meta‐analyses and calculated weighted mean differences and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 33 publications
3
71
2
4
Order By: Relevance
“…Previous clinical studies have shown that the SGLT2i treatment decreases systemic BP [14,15]. However, there were no significant changes in systemic BP, IOP, or OPP in either untreated or SGLT2i-treated mice during the follow-up period in the current study (Figure 1).…”
Section: Discussioncontrasting
confidence: 53%
“…Previous clinical studies have shown that the SGLT2i treatment decreases systemic BP [14,15]. However, there were no significant changes in systemic BP, IOP, or OPP in either untreated or SGLT2i-treated mice during the follow-up period in the current study (Figure 1).…”
Section: Discussioncontrasting
confidence: 53%
“…We found that tirzepatide is superior in reducing HbA 1c compared with other injectable therapies, in particular basal insulin and once-weekly GLP-1 RAs. In addition, tirzepatide, even at the lowest maintenance dose of 5 mg, can reduce body weight to a greater extent compared with GLP-1 RAs including subcutaneous semaglutide which, in turn, has been shown to be superior to other glucose-lowering agents [ 28 ]. Notably, head-to-head data for tirzepatide vs GLP1 RAs are available only for dulaglutide 1.5 mg and semaglutide 1 mg. Higher doses of dulaglutide (3.0 mg and 4.5 mg) [ 29 ] have also received marketing approval for treatment of type 2 diabetes, while application for a label extension of semaglutide at the dose of 2.0 mg [ 30 ] has been submitted to the US FDA and has recently received a positive recommendation by the EMA.…”
Section: Discussionmentioning
confidence: 99%
“…Various meta‐analyses have confirmed the favourable effect of SGLT‐2 inhibitors both on metabolic and cardiorenal endpoints in patients with type 2 diabetes 1,2,25‐27 . However, to our knowledge, no single study has to date assessed the effect of sotagliflozin on a series of efficacy and safety outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors reduce hyperglycaemia, body weight, and blood pressure, and display a beneficial effect on cardiovascular and renal endpoints in patients with type 2 diabetes 1,2 . Treatment guidelines recommend SGLT‐2 inhibitors in patients inadequately controlled with metformin monotherapy, particularly for those with heart failure or chronic kidney disease 3 .…”
Section: Introductionmentioning
confidence: 99%